KEMAMPUAN MENULIS PUISI MENGGUNAKAN METODE JIGSAW SISWA KELAS X SMA NEGERI 9 PADANG - Nelli, Selvika Fitria; Khairani, Zuraida; Hayati, Najmi (STKIP Pesisir Selatan, 2024)
This research is motivated by: First, teachers pay less attention to the learning process of students. Second, the way teachers teach and process teaching materials is less innovative. Third, students have difficulty in expressing ideas in writing. The purpose of this study is to describe the ability to write poetry using the jigsaw method of class X students of SMA Negeri 9 Padang. This type of research is quantitative research with descriptive method. Thepopulation of this study were students of class X.E9 SMA Negeri 9 Padang. The data of this research is the score of the test results of writing poetry using the jigsaw method of class X students of SMA Negeri 9 Padang. Based on the results of the study, it is concluded as follows: First, the ability to write poetry using the jigsaw method of class X SMA Negeri 9 Padang students for diction indicators is good (B) with an average of 77.78 in the range (76-85%) on a scale of 10. Second, the ability to write poetry using the jigsaw method of class X SMA Negeri 9 Padang students for imagery indicators is classified as more than sufficient (LDC) with an average of 68.89 in the range (66-75%). Third, the ability to write poetry using the jigsaw method of grade X students of SMA Negeri 9 Padang for the majas indicator is sufficient (C) with an average of 56.67 within the range (56-67%) on a scale of 10. Fourth, the ability to write poetry using the jigsaw method of grade X students of SMA Negeri 9 Padang for the combination of the three indicators is sufficient (C) with an average of 63.34 within the range (56-65%) on a scale of 10.